HAEMATOLOGICAL PROFILE OF LAYING HENS AFTER NEWCASTLE DISEASE VACCINATION - Anak Agung Sagung Kendran; Gusti Ayu Yuniati Kencana (Buletin Veteriner Udayana, 2024)
Newcastle disease (ND) is a viral disease that can cause high mortality in chickens. Hundreds of chickens died due to ND disease. Morbidity and mortality due to ND disease is very large. Viral diseases cannot be treated with antibiotics. Therefore prevention can only be done by vaccination. However, vaccination failure often occurs, it has been proven that there are still many reports of ND cases. Thus, to find out early before sick chickens are attacked by ND, this research aims to determine the hematological profile including: RBC, Hb, HCT, MCH, MCHC, MCH, PLT, WBC, Eosinophils, Monocytes, Neutrophils and Lymphocytes. The research method was a field survey with purposive sampling with blood sampling as a repeat period. The research sample consisted of 40 laying hens, 30 of which were vaccinated with the active ND vaccine of the Lasota strain and 10 without vaccination. Blood samples were taken with anticoagulation four times, namely once pre-vaccination and three times post-vaccination. The data obtained were analyzed by means of variance followed by the Duncan test using SPSS version 25. The results of the study stated that RBC, Hb, HCT, MCV, Neutrophils and Lymphocytes were significantly different (P<0.05). Meanwhile MCV, MCHC, PLT, WBC, Eosinophils and Monocytes were not significantly different (P>0.05).